(untitled) (International Journal of Medical and Surgical Sciences, 2015)
The occlusal splints are most commonly used devices for the treatment of temporomandibular disorders and bruxism. A case report of a male patient with deep bite and bruxism, indicating two flat occlusal splints presents full coverage made up of rigid acrylic and permanent use for five months is described. Using both intraoral devices allowed restoring lost vertical dimension and protect teeth attrition, deprogram the musculature and establish a new mandibular positioning prior to treatment of oral rehabilitation.